Quality planning and assurance : principles, approaches, and methods for product and service development - Tang, He (Herman) (John Wiley & Sons, Inc., 2022)
"Quality planning has been a fundamental industrial practice for several decades, yet there are few comprehensive quality planning textbooks dedicated to the understanding of this subject at the undergraduate and graduate levels. In the quality field, professionals often consider Toyota as a role model for best practices. While one can learn Toyota quality for its principles, its specific practices are not necessarily applicable for every situation. In The Toyota Way to Service Excellence, Dr. Liker and Ross stated, "the Toyota Way training was designed to teach principles rather than specific methodology" (p.32). Similarly, this book focuses on the fundamental principles of quality planning, and extrapolates on their applications in various industries throughout each chapter. For current and future quality professionals, you can start learning these principles, with supporting application examples in this book, and later apply them towards your unique applications. Like one of my students said, "What I enjoyed most about this course was taking the information learned in this course and being able to utilize it within the industry that I currently work in.""--